2015
DOI: 10.1108/dpm-04-2014-0060
|View full text |Cite
|
Sign up to set email alerts
|

Does transformational leadership build resilient public and nonprofit organizations?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 49 publications
1
67
1
1
Order By: Relevance
“…When a disaster hits, organizations need to be prepared in order to continue their core functions (Valero et al 2014). Otherwise, the safety and well-being of a community may be compromised when public organizations are charged with providing essential public services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a disaster hits, organizations need to be prepared in order to continue their core functions (Valero et al 2014). Otherwise, the safety and well-being of a community may be compromised when public organizations are charged with providing essential public services.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has found, for instance, that transformational leadership has a positive impact on the resiliency of organizations during a disaster (Valero et al 2014). Transformational leaders seek to build organizational resiliency through initiating disaster preparedness such as educating the public and by ensuring that organizational members are aware of plans for emergency response.…”
Section: South Koreamentioning
confidence: 99%
“…Valero, Jung, and Andrew (2015) posit that to respond effectively to public sector uncertainties and state emergencies, leaders need to be able to 'motivate, communicate, and articulate an organisation's mission' to followers (p. 4). Not surprisingly, the authors go on to associate transformational leadership with organisational resilience (Valero et al, 2015). Harland et al (2005) also found that particular dimensions of both transactional and transformational leadership can potentially contribute to resilience in subordinates.…”
Section: Leadershipmentioning
confidence: 99%
“…There are various critical factors for the organizations involved in relief operations such as trust, agility, IT use, flexibility, and adaptability. Understanding factors that improve the performance of organizations during relief operations, continues to be a timely and critical area of research (Valero, Jung, & Andrew, 2015). This study is expected to provide smaller organizations with guidelines for understanding the crucial factors to enhance the performance of humanitarian supply chain (HSC).…”
Section: Introductionmentioning
confidence: 99%